Legal Implications of International Digital Trade Agreements on Personal Data Protection in Foreign Investment in Southeast Asia - Laksito, Joni; Rahmawati, Amanda; Hasibuan, Ibnu Habibi; Fahriawan, Hendra (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
Digital transformation enhances cross-border economic integration through digital trade agreements, such as DEPA, CPTPP, or RCEP, which contain provisions for personal data protection. Southeast Asia, however, still experiences significant regulatory harmonization challenges due to country disparities in laws. This study examines the legal implications of international digital trade agreements on personal data protection systems in Indonesia, Thailand, and the Philippines, as well as their potential impact on the foreign investment climate in these countries. This research uses a normative-comparative juridical approach based on the analysis of 30 purposively selected international and national legal documents. As the Study Findings show, Thailand has the highest level of coherence with international norms concerning data protection, followed by Indonesia (73%) and then the Philippines (54%). This research also proves that legal certainty in data protection has a direct correlation with foreign investment growth in the digital sector. By innovatively contending a new integrated analytical model to link digital trade law and personal data protection, this research contribution offers strategic recommendations for regulating that harmonize the ASEAN region to bolster the secure and inclusive digital investment ecosystem.